Accuracy of Patient and Care Partner Identification of Cognitive Impairments in Parkinson's Disease–Mild Cognitive Impairment. Issue 5 (29th March 2016) - Copeland, Jacquelynn N.; Lieberman, Abraham; Oravivattanakul, Srivadee; Tröster, Alexander I.
Abstract: Background: Criteria for Parkinson's disease–mild cognitive impairment require a caregiver or patient complaint or clinician observation of cognitive decline and objective evidence of cognitive deficit in at least 1 of 5 cognitive domains. This study examines the accuracy of Parkinson's disease‐mild cognitive impairment patient and care partner reports of specific cognitive difficulties. Methods: A total of 42 Parkinson's disease–mild cognitive impairment patients and their care partners reported the absence or presence of deficits in each cognitive domain during an interview. A deficit in each domain was defined by scores ≤ 1.5 standard deviations below the mean on corresponding cognitive tests. Results: Sensitivity, specificity, and positive and negative predictive values were modest for patient and care partner reports across all domains. Patients' and care partners' accuracy in observing objectively identified deficits was poor across all domains (≤ 60% agreement; κ ≤ .07). Patient and care partner reports showed moderate agreement in all domains except attention (≥ 74% agreement; κ ≥ .43). Conclusions: Parkinson's disease–mild cognitive impairment patients and their care partners may not be accurate in identifying specific cognitive deficits. Thus, even patients (and care partners) who correctly report having a cognitive deficit may misidentify the specific deficit. The finding supports the value of International Parkinson and Movement Disorder Society Parkinson's disease–Mild Cognitive Impairment Level II assessment and cautions against relying on subjective report or screening in research in which the nature of cognitive deficit identification or treatment is paramount. Overreliance on patient and care partner reports of specific impairments may distort epidemiologic estimates of mild cognitive impairment subtypes and misdirect cognitive rehabilitation at incorrect domains. © 2016 International Parkinson and Movement Disorder Society